Crossing the dotted line : cultural divides - Bevelander, Dianne (SAGE Business Cases., 2015)
This case study is about the gender, cultural, and organizational issues that arise when Sema Isaura-Mans begins a new job as an account manager in a Dutch company. At first she enjoys the informal conversation between team members however, she soon becomes the butt of the joke due to short stature. After one meeting the matter comes to a head and Sema must decide how to proceed.